ChemInform Abstract: Explaining Stability of Transition Metal Carbides — and Why TcC Does Not Exist. Issue 18 (April 2016) - Wang, Qinggao; German, Konstantin E.; Oganov, Artem R.; Dong, Huafeng; Feya, Oleg D.; Zubavichus, Ya. V.; Murzin, V. Yu.
Abstract: The formation of transition metal (M) carbides Mx Cy and trends of their stability are systematically investigated using the USPEX code within the DFT.